Plant Diversity and Ecological Indices of Naturally Established Native Vegetation in Permanent Grassy Strips of Fruit Orchards in Southern Romania - Sina Cosmulescu; Florin Daniel Stamin; Daniel Răduțoiu; Nicolae Constantin Gheorghiu (Diversity, 2025)
This paper assesses the complexity and diversity of vegetation in grassy strips with spontaneous plants between tree rows in three fruit orchards (plum, cherry, apple) in Dolj County, Romania, using structural and biodiversity indices. It addresses the lack of data on spontaneous vegetation in Romanian orchards, supporting improved plantation management and native biodiversity conservation. The study found that grassy strips supported high wild herbaceous diversity and a complex, heterogeneous ecological structure, with the apple orchard showing the highest biodiversity. Species diversity, evaluated through species richness, evenness, and diversity indices (Shannon, Simpson, Menhinick, Gleason, etc.), showed species richness ranging from 30 species in the cherry orchard to 40 in the apple orchard. Several species, including Capsella bursa-pastoris, Geranium pusillum, Poa pratensis, Veronica hederifolia, Lolium perenne, and Convolvulus arvensis, were present in 100% of samples, making them constant species from a phytosociological perspective. Their presence indicates relatively stable plant communities in each orchard. From a phytocoenological view, an ecological plant community is defined not only by species composition but also by constancy and co-occurrence in sampling units. Dominance remained low in all orchards, indicating no single plant dominated, while evenness showed a uniform distribution of species.